1985
DOI: 10.1002/ajh.2830190409
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cerebral thrombosis in fletcher factor (prekallikrein) deficiency: A case report

Abstract: Despite markedly prolonged activated partial thromboplastin times (APTT) patients with Fletcher factor (prekallikrein) deficiency do not clinically bleed. However, there is one reported case of myocardial infarction associated with prekallikrein deficiency. These clinical observations suggest that the contact mechanism has a minor role in normal in vivo hemostatic function. We report a further two cases of prekallikrein deficiency in Caucasian siblings. The propositus presented with multiple cerebral thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 26 publications
0
20
0
3
Order By: Relevance
“…They belonged to 56 separate kindreds [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. A thrombotic event was reported in 9 of these patients belonging to 6 different families (table 1) [5,16,22,23,24,28]. …”
Section: Resultsmentioning
confidence: 99%
“…They belonged to 56 separate kindreds [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. A thrombotic event was reported in 9 of these patients belonging to 6 different families (table 1) [5,16,22,23,24,28]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, FXII and prekallikrein have also been shown to contribute to the development of experimental thrombosis in mice, 22,23 despite the normal to possibly prothrombotic phenotype associated with deficiency of either of these proteins (Hagemen trait and Fletcher trait, respectively) in humans. 14,[24][25][26] We previously demonstrated that FXI deficiency was associated with improved survival and reduced coagulopathy relative to wild-type mice during polymicrobial peritoneal sepsis. 27 The data suggested that FXI activity may have contributed to the pathogenesis of abdominal sepsis by promoting DIC.…”
mentioning
confidence: 99%
“…Recovery from the operation was normal as expected. A rare case of cerebral thromboses in Fletcher factor was reported by Harris et al (1985).…”
Section: Discussionmentioning
confidence: 99%